Physical Therapy Approaches for the Treatment of Iliotibial Band Syndrome: A systematic review - Evgenia Trevlaki; Sofia Dimitriadou; Emmanouil Trevlakis (International Journal of Advanced Health Science and Technology, 2022)
Iliotibial band syndrome (ITBS) is a common overuse injury, which involves lateral knee pain after activities with repetitive knee flexion and extension. It’s typically seen in athletes especially runners, cyclists as well as in triathlon. This syndrome is an inhibiting factor that affects the athlete’s participation, results and performance. This study aimed to investigate the efficacy of physical therapy methods and techniques in ITBS management. A computerized research was conducted in Google Scholar, PubMed and PEDro. A total of 14 studies were included. GT mobilization showed pain relief and negative Ober’s test. Self-stretch of the ITB with a FR contributes to short-term increases in flexibility. Deep transverse frictions did not seem to modify symptoms and are not recommended as a therapeutic approach. Therapeutic currents reduce pain in an average of 2 days. Trigger point release showed a significant decrease in pain and an improvement in function ability. The comparison of shockwave therapy and soft tissue mobilization techniques led to pain reduction without significant difference, while the comparison of dry needling and shockwave therapy showed improvement in pain and limb function in both groups. Research has shown that physical therapy approach can include many techniques and methods for a successful treatment of ITBS. Further research is needed in order to fully examine the effects of each treatment in large number of patients with ITB.